SOCIAL MAPPING PRANATA EKONOMI PADA KOMUNITAS LOKAL KAWASAN PESISIR (Sebuah Studi Di Desa Kuala Lama, Kecamatan Pantai Cermin, Kabupaten Serdang Bedagai, Provinsi Sumatera Utara) - Mochamad Syawie (Puslitbangkesos Kementerian Sosial RI, 2010)
In the past the need for economic institutions that govern trade patterns is not considered as urgent and important. Each family generally used to meet their need using their own crop, so there's hardly any possibility to came across the interest of other. The economic development of local communities tend to become more complex, while on the other hand the amount of goods and services that are available relatively limited and became more rare, causes the need for a more detailed economic institutions can no longer be sided. The main study in this research is there are no comprehensive economic institutions mapping available to provide a picture of existing economic institutions in a local community in coastal area. The purpose of this study is to get qualitative data about the existence of economic institutions on local communities in that coastal area. The method used in this study is qualitative research method. The informant involved in this study consisted of formal individual (Desa Kuala Lama Apparatus, Camat Pantai Cermin and the Chairman of BPD/ Village Consultative Body) and informal leader (community leaders and leaders of localÂ economic group). The location of this study is in Desa Kuala Lama, Kecamatan Pantai Cermin, Sserdang Bedagai. The result of this research revealed that there is strong indication that the existing economic institutions have a relatively significant role and, to certain limit, tend to overcome minimum basic needs for everyday lives.